2016
DOI: 10.1002/cncy.21800
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver reproducibility of cytologic p16INK4a/Ki‐67 dual immunostaining in human papillomavirus‐positive women

Abstract: Dual staining for p16 and Ki-67 demonstrated good reproducibility, confirming its robustness, which is a necessary prerequisite for its adoption as a triage test in cervical cancer screening programs that use human papillomavirus DNA as a primary test. Cancer Cytopathol 2017;125:212-220. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…It has been previously shown that p16/Ki-67 dual-stain shows substantial to good reproducibility with almost identical performance by novice evaluators compared with reference evaluations, indicating that it can be implemented in clinical practice with limited training. 34,35 The Kappa found in this study was lower as expected, this might be caused by the overall low quality of the samples. A disadvantage of the technique is that it cannot be reliably used on self-sampled material, as cellularity of cervical indicator cells in these samples is too limited resulting in a low sensitivity.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…It has been previously shown that p16/Ki-67 dual-stain shows substantial to good reproducibility with almost identical performance by novice evaluators compared with reference evaluations, indicating that it can be implemented in clinical practice with limited training. 34,35 The Kappa found in this study was lower as expected, this might be caused by the overall low quality of the samples. A disadvantage of the technique is that it cannot be reliably used on self-sampled material, as cellularity of cervical indicator cells in these samples is too limited resulting in a low sensitivity.…”
Section: Discussionmentioning
confidence: 39%
“…Partial HPV genotyping was done by the Roche Cobas 4800 test, according to the manufacturer's recommendations in the laboratory of the Department of Medical Microbiology, Radboud university medical center 26. This test provides separate result for HPV16 and 18, and a pool of 12 other high-risk HPV types (ie,31,33,35,39, 45, 51, 52, 56, 58, 59, 66, and 68). The HPV genotyping results were…”
mentioning
confidence: 99%
“…It has been argued that the dual stain can reduce the requirement for “expert” cytology through simplifying interpretation and may improve interoperator variability compared to traditional cytology . However, a recent study showed important differences in interobserver reproducibility according to a laboratory's experience highlighting the need for robust training and quality assurance . In summary p16/ki67 dual stain is a credible tool for risk stratification of HPV‐positive women and compares favorably to cytology .…”
Section: ±P16 ± Ki67mentioning
confidence: 99%
“…21 In ATHENA, and other studies, DS testing demonstrated better performance (improved sensitivity and at least equal specificity) compared to cytology for the cross-sectional detection of ≥CIN3 in hrHPV-positive women. 20,[22][23][24][25][26][27][28][29][30][31] However, like Pap cytology, DS testing is not integrated into the first-line HPV screening test, and both Pap cytology and DS testing require the preparation of a slide for subjective microscopic assessment by highly trained professionals.…”
Section: Introductionmentioning
confidence: 99%